2019
DOI: 10.1016/j.jvs.2018.05.218
|View full text |Cite
|
Sign up to set email alerts
|

Early results with the custom-made Fenestrated Anaconda aortic cuff in the treatment of complex abdominal aortic aneurysm

Abstract: Treatment with this specific custom-made fenestrated aortic cuff is feasible after complicated previous (endovascular) aortic repair or in complex AAAs. The complexity of certain AAA cases is underlined in this study, and the Fenestrated Anaconda aortic cuff is a valid option in selected cases in which few treatment options are left.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…A different study by the same group reported 99 ± 1% and 88 ± 6% TVP at 1 and 2 years, respectively. 37 Similarly, Dijkstra et al 16 found that primary patency in their study was 96% at 1-month post-EVAR while TVP was 98.1%. Importantly, three studies [12][13][14] reported 100% TVP with another six studies 16,21,[27][28][29]31 achieving a TVP rate of ≥ 98%.…”
Section: (86% Ts)mentioning
confidence: 74%
See 2 more Smart Citations
“…A different study by the same group reported 99 ± 1% and 88 ± 6% TVP at 1 and 2 years, respectively. 37 Similarly, Dijkstra et al 16 found that primary patency in their study was 96% at 1-month post-EVAR while TVP was 98.1%. Importantly, three studies [12][13][14] reported 100% TVP with another six studies 16,21,[27][28][29]31 achieving a TVP rate of ≥ 98%.…”
Section: (86% Ts)mentioning
confidence: 74%
“…A 2018 study by the same group identified 14 out of 27 patients with stable or decreased aneurysm sac diameters. 37 To further ascertain the Fenestrated Anaconda™'s outstanding aortic remodelling results, Freyrie et al 17 observed AAA shrinkage of > 5 mm in 130 out of 177 patients (73.4%), with only seven patients (4%) showing AAA sac enlargement. Furthermore, Stehr et al 39 reported a substantial reduction of the median aneurysm diameter from 56.7 to 49.0 mm after 6 months ( P = 0.05).…”
Section: The Terumo Aortic Anaconda™ Sgmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Importantly, 7 Fenestrated Anaconda™ studies identified within the literature achieved TVP of >97%, a summary of which can be found in Table 6. 20,23,28,37,[38][39][40] On the other hand, the aforementioned Oderich et al 31 reported 95.2 ± 1.9% and 82.7 ± 4.1% primary TVP at 1 and 5 years, respectively, using Zenith. While Sveinsonn et al 41 achieved 96.4% and 94.0% primary TVP with Zenith after 1 and 5 years, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…To address this issue several options have been proposed, including treatment with fenestrated cuffs sealing in the preexisting main body, which may however lead to type III endoleaks or complete relining of the previous endograft with use of a bifurcated distal component featuring an inner limb. 14 The latter option minimizes the overlap of the bifurcated to the fenestrated component as well as to the contralateral iliac limb also potentially leading to type III endoleaks. One advantage of this branched design is that distal landing is achieved on the ipsilateral side with the tapered main body and on the contralateral side with a bridging stent-graft to the respective limb through the additional branch.…”
Section: Discussionmentioning
confidence: 99%